Acronyms of dying versus patient autonomy - Salkić, Anna; Zwick, Anna (European journal of health law, 2012)
Abstract: In medical practice in Germany and several other countries abbreviated orders linked to end-of-life decisions, such as DNR (do not resuscitate), are increasingly used. In order to investigate their legal status, this article gives an overview of the recently passed German law, which regulates the process of end-of-life decision-making and the use of living wills, giving primacy to patient autonomy. Concerning the risk of misinterpretation of acronyms, the article describes the impacts of such orders on patient autonomy and safety and suggests a clear systematic classification of the different DNR orders in order to investigate their legal status under the German law. Their general binding force is to be acknowledged, depending on its origination and the fulfilment of certain requirements.
Gesehen am 21.06.2018